Network analysis reveals rare disease signatures across multiple levels of biological organization - Pisanu Buphamalai (Nature Portfolio, 2021)
Despite the clear causal relationship between genotype and phenotype in rare diseases, identifying the pathobiological mechanisms at various levels of biological organization remains a practical and conceptual challenge. Here, the authors introduce a network approach for evaluating the impact of rare gene defects across biological scales.